Kaidah Al-‘Adatu Muhakkamah: Konsep, Aplikasi, dan Relevansi dalam Dinamika Hukum Islam Kontemporer - Samsudin Buamona B (Sekolah Tinggi Agama Islam Babussalam Sula, 2024)
The principle of Al-‘Adatu Muhakkamah is a fundamental concept in Islamic law that recognizes customary practices as a source of law, provided they do not contradict Sharia principles. This article examines the concept, legal foundation, and application of this principle in various fields, such as family law, muamalah, and siyasah. Using a literature review method, the findings reveal that this principle offers flexibility within Islamic law to accommodate local traditions, such as customary marriage practices and business transactions rooted in local customs, as long as they adhere to Sharia requirements. However, its application is not absolute, as it must consider the limitations imposed by Sharia principles, such as prohibiting practices inconsistent with Islamic values, such as political dowries. The study further highlights the need for renewed understanding and empirical research on this principle to address the challenges of modernization. In conclusion, Al-‘Adatu Muhakkamah serves as a vital guideline that ensures the relevance of Islamic law while preserving local traditions, provided both align with the overarching objectives of Sharia.